2007
DOI: 10.1146/annurev.nutr.27.061406.093726
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Food Intake Repression in Indispensable Amino Acid Deficiency

Abstract: Animals reject diets that lead to indispensable amino acid (IAA) depletion or deficiency. This behavior is adaptive, as continued IAA depletion is incompatible with maintenance of protein synthesis and survival. Following rejection of the diet, animals begin foraging for a better IAA source and develop conditioned aversions to cues associated with the deficient diet. These responses require a sensory system to detect the IAA depletion and alert the appropriate neural circuitry for the behavior. The chemosensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 107 publications
3
108
0
2
Order By: Relevance
“…According to Black et al (1986) and Pitroff and Kothmann (2001), pigs and ruminants adjust feed intake based on dietary energy. Others (Henry 1985;Simpson et al 2003;Gietzen et al 2007;Gilbert et al 2008) directly involve protein intake and quality or the protein-energy ratio as the most important nutrient in regulating food consumption. In a recent review, Raubenheimer and Simpson (2007) showed that the variance of the responses of animals to nutrient status can be accounted for by the macronutrient (proteins, carbohydrates and fats) balance.…”
mentioning
confidence: 99%
“…According to Black et al (1986) and Pitroff and Kothmann (2001), pigs and ruminants adjust feed intake based on dietary energy. Others (Henry 1985;Simpson et al 2003;Gietzen et al 2007;Gilbert et al 2008) directly involve protein intake and quality or the protein-energy ratio as the most important nutrient in regulating food consumption. In a recent review, Raubenheimer and Simpson (2007) showed that the variance of the responses of animals to nutrient status can be accounted for by the macronutrient (proteins, carbohydrates and fats) balance.…”
mentioning
confidence: 99%
“…Furthermore, there is evidence in the literature that rats reject diets deficient in indispensable amino acids. As a result, the food intake of the animals is lower than their energy requirements 24 . This was confirmed in the present study as the G 10 group rejected more than half (57.6%) of the diet offered.…”
Section: Discussionmentioning
confidence: 97%
“…In the classical behavioral test for EAA deficiency, animals detect and reject a diet lacking an EAA [69]. Indeed, animals detect and reject their first EAAdeficient meal within 20 min [70]. Lesion studies have shown that an intact anterior piriform cortex (APC) is essential for the detection of EAA deficiency in vivo [71].…”
Section: Sensing Of Amino Acids Deficiency In the Central Nervous Sysmentioning
confidence: 99%